Educational Background Disclosure and Institutional Transparency: Evidence from Parliamentary Profiles in Indonesia - Priyo Budi Santoso (Policy, Law and Political Research Center, 2026)
Public trust and institutional transparency are primary foundations for healthy democratic governance. In the Indonesian parliament (DPR-RI), public concern has arisen over the lack of transparency regarding parliamentarians’ educational backgrounds. This essay tested the level of educational disclosure among parliamentarians and its implications for institutional governance. The approach used is descriptive-qualitative, and content analysis based on secondary data. The results indicate that the proportion of members listing advanced education remains limited, and some profiles are incomplete. It raises questions about parliamentarians’ readiness to address the complexities of public policy and underlines the need for greater transparency. The lack of educational disclosure has the potential to impact public perceptions of meritocracy and accountability as the foundations for parliamentary capacity in Indonesia. In summary, these findings recommend strengthening internal regulations to require comprehensive disclosure of educational backgrounds and developing members’ capacity in law, public policy, and other fields relevant to addressing the country’s issues. It can strengthen legislative quality and support democratic governance.